Pre-design of bottom ash cooling using CFD simulation: a case study of the coal generator power plant in the PT. BEST Tanjung Enim of South Sumatera - Ozkar F. Homzah; Ella Sundari; Muhammad Irfan Dzaky; Firdaus .; Fatahul Arifin; Damar Adji Prayoga; Kabul Andi Setiyadi; Kabul Kabul (Jurnal Polimesin, 2024)
The manual removal of bottom ash from the boiler is a hazardous activity due to the extremely high temperatures involved, ranging from 700 to 800°C. The objective of this research is to develop a cooling device to facilitate the bottom ash removal process for workers at PT. BEST Tanjung Enim and to measure the reduction in ash temperature achieved by cooling device. The design was created using computer aided design software and Computational Fluid Dynamics (CFD) simulations. Subsequently, a hypothesis is proposed, defining the bottom ash material as Silicon Dioxide (SiO₂) and equalizing the density of the bottom ash. To ascertain the temperature drop, variations in the screw conveyor’s rotation speed were tested at 40, 33, and 12 rpm, paired with cooling water velocities of 0.5, 0.75, and 1 m/s respectively. The findings of study indicated that a screw conveyor speed of 12 rpm combined with a cooling water velocity of 0.5 m/s yielded the lowest bottom ash temperature, reaching 402°C, thus significantly reducing the need for manual handling when the ash temperature remains at 800°C. Further study should explore the application of Discrete Element Method (DEM) simulations for modelling bulk material behaviour and the integration of additional cooling media to enhance system performance.